Electronic structure tuning during facile construction of two-phase tungsten based electrocatalyst for hydrogen evolution reaction. (1st September 2018) - Shi, Meiqin; Li, Wang; Fang, Jun; Jiang, Zhuangzhuang; Gao, Jing; Chen, Zhaoyang; Sun, Fanfei; Xu, Yinghua
Abstract: Fabrication of effective electrocatalysts combining two pure phases including carbide and phosphide with a certain proportion by the clean and simple strategies still remain a challenge. Here we synthesized tungsten carbide/tungsten phosphide-coated N-doped carbon (W2 C/WP@NC) by one-step pyrolysis process without participation of PH3 . In this synthesis process phosphotungstic acid, a heteropolyacid provided P and W atoms while 2, 6-diaminopyridine, a heterocyclic compound with strong alkalinity acted as C and N source. 2, 6-diaminopyridine was carefully chosen because it made a contribution to the complete decomposition of phosphotungstic acid where WO4 2− and PO4 3− groups were formed which both were essential to formation of WP phases. An overpotential of 83 mV which was required to achieve a current density of 10 mA cm −2 in 0.5 M H2 SO4 exhibited the high electrocatalytic activity of W2 C/WP@NC catalyst in hydrogen evolution reaction (HER). The weight ratio of W2 C to WP was calculated by Rietveld refinement and near edge X-ray absorption fine structure (XANES). W L3 -edge XANES spectra of different samples confirmed that little amount of WP could tune the electron state on W species. The enhanced HER performance was attributed to the favorable electron distribution on W species in W2 C/WP@NC which approached to the balance between H-atom adsorption and desorption. Graphical abstract: The XANES and polarization curves of HER for the different catalysts. Image 1